Using community forest management to achieve REDD+ goals - Agrawal, A.; Angelsen, A. (Center for International Forestry Research, 2009)
Policy makers can improve the likelihood of success for REDD+ initiatives by incorporating success factors identified through decades of research on community forest management. These include sufficient size and clear boundaries of forests, predictability of benefit flows, local autonomy in designing clear and enforceable rules for access and use of forests, and provisions for monitoring and sanctioning rule violations. REDD+ outcomes can be enhanced by selecting existing and new community forest management sites with user group and contextual characteristics associated with successful forest outcomes. These include a stable technological and policy environment, low levels of intergroup conflict, and small to medium-sized, forest-dependent user groups that have management experience. Community buy-in and participation increase the 3Es+ and therefore the sustainability of REDD+ projects.